Feeding rate of freshwater eel Anguilla bicolor bicolor: at the body weight of 1–2 g - Fekri, Latifa; Affandi, Ridwan; Budiardi, Tatag (Indonesian Society of Scientific Aquaculture (ISSA), 2014)
ABSTRACT The aim of the research was to determine feed requirement for the maintenance, optimum, and maximum growth of freshwater eel (Anguilla bicolor bicolor) seed (1–2 g body weight). Feed used in this research was KRA feed with 46% protein content, with different feeding level (FR) at 0%, 5%, 10%, and 15% of fish biomass. The experiment was conducted in 30 days. Parameters measured were survival and specific growth (SGR). The results showed that survival of fish in all treatments were 100%, except in fish fed on 15% of biomass (only 96). Fish growth with feeding of 0%, 5%,10%, and 15%, were -1.06%; 0.42%; 0.73%; and 0.19%, respectively. Based on the analysis of the relationship between feeding level and growth, the feed requirement for maintenance, optimum, and maximum growth in 1–2 g freshwater eel seed were 3.3%; 7.0%; and 9.5% of the biomass, respectively. Keywords: eel seed, feed requirement, growth ABSTRAK Penelitian dilakukan dengan tujuan untuk mendapatkan kebutuhan pakan untuk maintenance, dan untuk pertumbuhan optimum serta maksimum benih ikan sidat (Anguilla bicolor bicolor) (bobot tubuh 1–2 g). Pakan yang digunakan pada penelitian ini adalah pakan KRA dengan kadar protein 46%, dengan tingkat pemberian pakan 0%, 5%, 10%, dan 15% dari bobot biomassa ikan. Pemeliharaan berlangsung selama 30 hari. Parameter yang diukur meliputi sintasan (STS) dan laju pertumbuhan spesifik (LPS). Hasil penelitian menunjukkan bahwa STS benih ikan sidat selama pemeliharaan, memiliki nilai yang baik (100%) kecuali pada pemberian pakan 15% (hanya 96%). Laju pertumbuhan benih ikan sidat selama pemeliharaan dengan pemberian pakan 0%, 5%, 10%, dan 15% berturut-turut adalah -1,06%; 0,42%; 0,73%; dan 0,19%. Berdasarkan analisis hubungan antara tingkat pemberian pakan dan laju pertumbuhan spesifik, maka kebutuhan pakan maintenance, pertumbuhan optimum dan maksimum benih ikan sidat berukuran 1–2 g berturut-turut adalah 3,3%; 7%; dan 9,5% dari biomassa. Kata kunci: benih ikan sidat, kebutuhan pakan, pertumbuhan